Swelling, Thermal, and Shear Properties of a Waste Tire Rubber Based Magnetorheological Elastomer - Ubaidillah,; Purnomo, Endra Dwi; Ismail, Hanafi; Choi, Seung-Bok; Aziz, Aishah Abdul; Mazlan, Saiful Amri (Frontiers in Materials, 2019)
In this study, the achievement of revulcanization, thermal stability and rheological behaviors of waste tire rubber (WTR) based magnetorheological elastomers (MREs) were evaluated to convince their applicability as one of smart material possessing the field-dependent tuning capability of material characteristics such as complex modulus. The cross-linking density of the In this study, the achievement of revulcanization, thermal stability and rheological behaviors of waste tire rubber (WTR) based magnetorheological elastomers (MREs) were evaluated to convince their applicability as one of smart material possessing the field-dependent tuning capability of material characteristics such as complex modulus. The cross-linking density of the MREs was assessed through a swelling test to ratify the degree of reclaiming. The behavior of MREs to the temperature enhancement was evaluated via thermogravimetric analysis and thermomechanical analysis. Meanwhile, the alteration of shear stress depending on the magnetic fields was investigated at both steady and oscillatory states measurement using a rheometer. It has shown that the increment of shear stress is proportional to the increment of the magnetic field. More specifically, it has found that the WTR based MRE can achieve the maximum static stress ranging from 9 to 13 kPa (at 656 mT) with a linear viscoelastic (LVE) region above 3% strain amplitude. Also, form the oscillatory test it has determined that the highest MR effect of 24.71 % is achieved which directly indicates the augmentation of both storage and loss moduli under ramped frequency and strain. Finally, it has investigated that the highest degree of reclamation based on the swelling test is achieved up to 54 % confirming the occurrence of the crosslinking during the reclamation process.